Data infrastructure for next-gen finance : tools for cloud migration, customer even hubs, governance & security - Roberts, Jane (O'Reilly Media, 2016)
Stricter regulations and changing technology have forced financial services organizations to make major changes in the way they handle sensitive data. With a focus on engineering and infrastructure, this O'Reilly report examines the tools and best practices that leading financial firms are using to migrate data to the cloud, build customer event hubs, and adhere to new rules for governance and security. Based on talks given at recent Strata + Hadoop World events, this detailed report explains how Capital One, MasterCard Advisors, and the Financial Industry Regulatory Authority (FINRA) tackled major data projects with help from technology leaders such as Cloudera and Intel. Learn how FINRA migrated their portfolio from a data warehouse to the Hadoop cloud ecosystem Understand what's required to support data governance in finance, and learn about the infrastructure Capital One implemented Delve into Hadoop's security maturity model, compliance-ready security controls, and enterprise data hub for preventing breaches Examine the architecture of a Customer Event Hub, a tool that's pushing the boundaries of how organizations interact with customers.